Asosiasi Representatif Sebagai Humor dalam Ceramah Ustaz Abdul Somad Dari Persaudaraan Menuju Kebangkitan - Mahmudah, Winda Woro (LP. Ma'arif Janggan Magetan, 2024)
This article discusses the use of representative associative speech style in Ustaz Abdul Somad's (UAS) sermons as a means to create humor while delivering religious advice. This linguistic style employs indirect comparisons to clarify meanings and enhance audience comprehension. The study adopts a functional pragmatic analysis method, with data derived from UAS's sermon themed